Kinerja ASN Dalam Perspektif Kompetensi dan Insentif - Diyana Lestari, Ni Putu; Kawiana, I Gede Putu; Atim Purwaningrat, Putu (WidyaAmrita: Jurnal Manajemen, Kewirausahaan dan Pariwisata, 2024)
Performance is a reflection of individual performance, and when each individual works well, performs well, is enthusiastic and gives their best, this is the answer to the success or failure of an organization’s goal setting. This study was conducted to determine the impact of Tabanan Regency Environmental Services capabilities and incentives on the performance of her ASN employees. The study population consisted of a sample of all Tabanan Regency Environmental Services ASN staff, a total of 125 individuals, a total of 125 respondents, and the sampling method used a saturated sample. Data for this study were collected through the distribution of questionnaires, and the tools used in this study were validity test, reliability test, classical assumptions, multiple regression analysis, coefficient of determination, t-test, and F-test. . In this study, we find that: Capabilities and incentives have a large positive impact on employee performance. The magnitude of the independent variable’s effect on employee performance is 60.9%. Based on the survey results, Tabanan Environmental Service should implement outbound and other field activities in the future to motivate employees. Such activities calm employees down, reduce work stress, and make employees more engaged in their work.